Homogeneous analysis of globular clusters from the APOGEE survey with the BACCHUS code – II. The Southern clusters and overview. Issue 2 (16th December 2019) - Mészáros, Szabolcs; Masseron, Thomas; García-Hernández, D A; Allende Prieto, Carlos; Beers, Timothy C; Bizyaev, Dmitry; Chojnowski, Drew; Cohen, Roger E; Cunha, Katia; Dell'Agli, Flavia; Ebelke, Garrett; Fernández-Trincado, José G; et al.
ABSTRACT: We investigate the Fe, C, N, O, Mg, Al, Si, K, Ca, Ce, and Nd abundances of 2283 red giant stars in 31 globular clusters from high-resolution spectra observed in both the Northern and Southern hemisphere by the SDSS-IV APOGEE-2 survey. This unprecedented homogeneous data set, largest to date, allows us to discuss the intrinsic Fe spread, the shape, and statistics of Al-Mg and N-C anti-correlations as a function of cluster mass, luminosity, age, and metallicity for all 31 clusters. We find that the Fe spread does not depend on these parameters within our uncertainties including cluster metallicity, contradicting earlier observations. We do not confirm the metallicity variations previously observed in M22 and NGC 1851. Some clusters show a bimodal Al distribution, while others exhibit a continuous distribution as has been previously reported in the literature. We confirm more than two populations in ω Cen and NGC 6752, and find new ones in M79. We discuss the scatter of Al by implementing a correction to the standard chemical evolution of Al in the Milky Way. After correction, its dependence on cluster mass is increased suggesting that the extent of Al enrichment as a function of mass was suppressed before the correction. We observe a turnover in the Mg-Al anticorrelation at very low Mg in ω Cen, similar to the pattern previously reported in M15 and M92. ω Cen may also have a weak K-Mg anticorrelation, and if confirmed, it would be only the third cluster known to show such a pattern.